Microstructural characterisation of spray formed Si-30Al for thermal management applications - Hogg, S; Lambourne, A; Ogilvy, A; Grant, P (Elsevier, 2006)
This paper presents a study of the microstructure of a spray formed Si-30 wt.%Al alloy used in electronic packaging applications. The microstructure consisted of ~5μ equiaxed primary Si grains and a coarse grained Al-rich phase with occasional regions of ~10 μm equiaxed Al-rich grains interpenetrating the Si network with no evidence of a lamellar Al-Si eutectic. This unusual microstructure arose because of the particular solidification conditions during and immediately after the spray forming process and the large alloy freezing range.